Constructing Financial Literacy Indicators for Students: A Conceptual Mapping Approach - Napitupulu, Paradon; Siswandari, Siswandari; Hindrayani, Aniek; Sangka, Khresna Bayu (Universitas Sebelas Maret, 2025)
Financial literacy is an essential life skill that should be developed from an early age, especially amid growing digital economic complexity and increasing financial risks. However, existing indicators for assessing students’ financial literacy remain fragmented and lack alignment with the evolving conceptual landscape in global research. This study aims to construct a conceptual framework of financial literacy indicators for school-age students using a Conceptual Mapping approach supported by bibliometric analysis. Metadata from Scopus-indexed publications (2015–2025) were analyzed using VOSviewer to identify thematic structures and interconnections among key concepts. The analysis revealed that financial literacy, school children, and financial knowledge serve as central nodes, forming four main clusters: cognitive, affective, strategic, and instructional. The resulting framework highlights the multidimensional nature of financial literacy and offers a structured foundation for developing context-responsive assessment tools, curriculum models, and educational interventions. This study contributes to refining the theoretical understanding of financial literacy while providing practical implications for educators and policymakers.